Peningkatan Prestasi Belajar Matematika Siswa Kelas VIII Melalui Pembelajaran Sosial Emosional di SMPN 1 Takeran - Yohana Dea Wardani; Sanusi Sanusi; Sri Handayani (Departement of Mathematics Education, 2024)
This research was motivated by the low mathematics learning achievement and emotional social abilities of class VIII students at SMPN 1 Takeran. Low mathematics learning achievement can be seen through students' mathematics scores, while students' social emotional abilities can be seen through students' attitudes and social emotional questionnaire results. This research is classroom action research involving 24 class VIII students. The aim of this research is to improve the mathematics learning achievement of class VIII students at SMPN 1 Takeran by implementing social emotional learning. Researchers used data collection techniques in the form of tests, questionnaires and interviews. From the research results, it was found that social emotional abilities influence students' mathematics learning achievement. The results showed that students' initial mathematics learning achievement (average 64.83, percentage of learning completeness 54%) increased in cycle I (average 72.17, percentage of learning completeness 71%) then increased again in cycle II (average average 77.88, percentage of learning completeness 83%). There was an increase in learning achievement from cycle I and cycle II, with an increase in the percentage of success of 12% and an average increase of 5.71. So, based on the analysis of research results, it can be concluded that the application of the social emotional learning approach to class VIII students at SMPN 1 Takeran succeeded in increasing mathematics learning achievement